Черные купола. Выстрел в прошлое. - Конторович Александр Сергеевич (А. Конторович. Только бестселлеры!, 2013)
Экземпляры: ФО-14 (20131126) / Инвентарный номер: 48689 / Цена: 149.80 / Сис.шифр: Р2 / Авт.знак: К 65 / ГРНТИ: 17.82 / ББК: 84(2Рос.Рус)6